2013
DOI: 10.1590/s1807-55092013000100007
|View full text |Cite
|
Sign up to set email alerts
|

Corrida em esteira e exercícios de força: efeitos agudos da ordem de realização sobre a hipotensão pós-exercício

Abstract: Este estudo analisou as respostas de pressão arterial sistólica (PAS) e pressão arterial diastólica (PAD) após duas sessões de exercício concorrente realizado em diferentes ordens [aeróbio-força (AF), e força-aeróbio (FA)]. Quinze indivíduos normotensos foram submetidos a duas sessões de exercício realizadas em dias distintos na seguinte sequência AF e FA. A PAS e PAD foram medidas antes e a cada 15 min durante 60 min de recuperação pós-exercício. Houve hipotensão pós-exercício (HPE) para PAS, aos 30 min (-7,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
6
1
1
Order By: Relevance
“…Additionally, low-intensity ST favours a greater number of repetitions and a longer time of muscular tension, which contribute to a better cardiovascular response due to the greater afferent muscular nervous stimulation, mediated by mechanisms associated to the mechanorreflex and metaborreflex controls (Cunha et al, 2013), which may have contributed to the appearance of PEH after P2. Santiago et al (2013) compared the influence of the exercises order (AT followed by ST and ST followed by AT) in blood pressure responses in normotensive individuals and found results that support those observed in the present study. The authors found PEH in SBP at 30 and 45 minutes post exercise in the AT session followed by ST.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, low-intensity ST favours a greater number of repetitions and a longer time of muscular tension, which contribute to a better cardiovascular response due to the greater afferent muscular nervous stimulation, mediated by mechanisms associated to the mechanorreflex and metaborreflex controls (Cunha et al, 2013), which may have contributed to the appearance of PEH after P2. Santiago et al (2013) compared the influence of the exercises order (AT followed by ST and ST followed by AT) in blood pressure responses in normotensive individuals and found results that support those observed in the present study. The authors found PEH in SBP at 30 and 45 minutes post exercise in the AT session followed by ST.…”
Section: Discussionsupporting
confidence: 88%
“…e present study also found PEH, nonetheless, this e ect was only observed at the 45th min of post-exercise recovery after the RA session, and in the 1-hour mean values (p < 0.02). S et al 24 found results that di ered from the ones shown in the present study. ey performed two di erent models of CE in 15 young adults (men and women), being: 1) AE (80% of heart rate reserve) followed by RE (3 sets of 8 repetitions at 75% of 1RM); and 2) RE followed by AE using the same intensities.…”
Section: Discussioncontrasting
confidence: 51%
“…In addition, the training routine should combine strength and aerobic exercises, because improvements occur both in cardiorespiratory fitness as in mass and muscularstrength 28 . Moreover, studies that have analyzed BP after a session of combined training are scarce and are usually conducted in healthy subjects 16,17,19,29,30 . Keeseet al 17 analyzed healthy men (20-30 years) submitted to four experimental sessions.…”
Section: Discussionmentioning
confidence: 99%
“…BP reduction after an acute exercise session has been associated with chronic reduction of resting BP 11,12 . These BP reductions after exercise were demonstrated in hypertensive individuals 13,14 , individuals with SM 15 , normotensive individuals 16,17 and after aerobic exercises 13,17 and inresistanceexercise (RE) 15,17,18 . In fact, more recently, some studies have found that PEH also occurs after the combination of aerobic (AE)and strength exercise.…”
Section: Introductionmentioning
confidence: 90%